2021
DOI: 10.1111/mila.12361
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal trust in children's testimonial learning

Abstract: Within the growing developmental literature on children's testimonial learning, the emphasis placed on children's evaluations of testimonial evidence has shielded from view some of the more collaborative dimensions of testimonial learning. Drawing on recent philosophical work on testimony and interpersonal trust, we argue for an alternative way of conceptualizing the social nature of testimonial learning. On this alternative, some testimonial learning is the result of a jointly collaborative epistemic activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 111 publications
(138 reference statements)
0
8
0
Order By: Relevance
“…Seminal research on children's social learning has shown that children factor in a history of epistemic accuracy when choosing who to learn from, trusting those who are more likely to have correct beliefs to share (e.g., Koenig & Harris, 2005;Koenig et al, 2004Koenig et al, , 2019Sobel & Finiasz, 2020). More recently, researchers have started to emphasize the importance of social and interpersonal processes that might affect children's trust (e.g., Koenig et al, 2021;Tong et al, 2020). Specifically, there is some evidence that starting from around 4 years of age, children prefer to learn from individuals based on their interpersonal and social characteristics, such as one's manner of address, being a native language speaker, or a prosocial agent (Kinzler et al, 2011;Lane et al, 2013;Li & Koenig, 2020).…”
Section: Social Relationships and Children's Selective Learningmentioning
confidence: 99%
“…Seminal research on children's social learning has shown that children factor in a history of epistemic accuracy when choosing who to learn from, trusting those who are more likely to have correct beliefs to share (e.g., Koenig & Harris, 2005;Koenig et al, 2004Koenig et al, , 2019Sobel & Finiasz, 2020). More recently, researchers have started to emphasize the importance of social and interpersonal processes that might affect children's trust (e.g., Koenig et al, 2021;Tong et al, 2020). Specifically, there is some evidence that starting from around 4 years of age, children prefer to learn from individuals based on their interpersonal and social characteristics, such as one's manner of address, being a native language speaker, or a prosocial agent (Kinzler et al, 2011;Lane et al, 2013;Li & Koenig, 2020).…”
Section: Social Relationships and Children's Selective Learningmentioning
confidence: 99%
“…Deciding whether and when to trust others is therefore a crucial task, and the development of this ability has been the subject of extensive investigation by child psychologists (for a review, Koenig et al, 2021). Exhaustively reviewing this literature would be beyond the scope of this brief research report.…”
Section: The Development Of Intent-based Epistemic Trustmentioning
confidence: 99%
“…Much research examines children's ability to estimate another person's knowledge, prior reliability, or expertise when evaluating their testimony (for reviews, see Brosseau‐Liard, 2017; Harris, Koenig, Corriveau & Jaswal, 2018; Sobel & Finiasz, 2020). Here, we focus on children's ability to participate in a range of social interactions that involve estimating a person's interpersonal commitments, abilities to hold both speakers and listeners accountable, and deciding how much to trust speakers who make such commitments (Pesch & Koenig, 2018; Koenig, Li & McMyler, 2022).…”
mentioning
confidence: 99%
“…In contrast, children also make a second type of decision, collaborative decisions that aim to settle questions like, “Are you asking me to take you at your word?,” “Can I hold you responsible for your words and actions?,” “If I mistrust your testimony, how will you feel in return?” When children make the first type of decisions, they are concerned with whether a speaker possesses sufficient knowledge or competence to make a given claim and whether these claims are sufficiently supported (e.g., do they have appropriate access to evidence; see Koenig, Tiberius & Hamlin, 2019). However, when they make the second type of decision, children are concerned with whether to take a person at their word in the context of an epistemic collaboration in which a speaker simply asks for a listener's trust, trust that can be given or withheld by the listener (for a larger discussion of the distinction between evidential learning and interpersonal trust, see Koenig, Li & McMyler, 2022; Koenig & McMyler, 2019). In cases of epistemic collaboration, testimonial learning is similar to joint action, as both involve working toward a shared goal through a social process that necessitates a mutual understanding of individual responsibilities within the collaborative activity.…”
mentioning
confidence: 99%